A Facile Method for Producing Selenocysteine‐Containing Proteins. Issue 24 (9th May 2018) - Mukai, Takahito; Sevostyanova, Anastasia; Suzuki, Tateki; Fu, Xian; Söll, Dieter
Abstract: Selenocysteine (Sec, U) confers new chemical properties on proteins. Improved tools are thus required that enable Sec insertion into any desired position of a protein. We report a facile method for synthesizing selenoproteins with multiple Sec residues by expanding the genetic code of Escherichia coli . We recently discovered allo‐tRNAs, tRNA species with unusual structure, that are as efficient serine acceptors as E. coli tRNA Ser . Ser‐allo‐tRNA was converted into Sec‐allo‐tRNA by Aeromonas salmonicida selenocysteine synthase (SelA). Sec‐allo‐tRNA variants were able to read through five UAG codons in the fdhF mRNA coding for E. coli formate dehydrogenase H, and produced active FDHH with five Sec residues in E. coli . Engineering of the E. coli selenium metabolism along with mutational changes in allo‐tRNA and SelA improved the yield and purity of recombinant human glutathione peroxidase 1 (to over 80 %). Thus, our allo‐tRNA UTu system offers a new selenoprotein engineering platform. Abstract : ′Allo ′Allo ! Selenocysteine (Sec) confers new chemical properties on proteins, and improved tools are thus required for the insertion of Sec into proteins. Genetic code expansion and protein engineering techniques were used to develop a system based on allo‐tRNAs that enables the efficient synthesis in E. coli of selenoproteins containing multiple Sec residues at defined positions.